2013
DOI: 10.1007/s11914-013-0174-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Radiation on Bone

Abstract: Ionizing radiation produces its deleterious biologic effects by both direct (DNA strand breaks) and indirect processes (formation of free oxygen radicals). Mitotically active cells are more susceptible to the detrimental effects of ionizing radiation. These effects are most severe locally within the treatment field but can also occur systemically, possibly reflecting hormonal influences and inflammatory cytokine mediators. Specific bone complications of radiation include osteopenia, growth arrest, fracture and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(53 citation statements)
references
References 23 publications
1
51
0
1
Order By: Relevance
“…14 Radiation has been shown to harm bone through numerous localized and systemic effects, often leading to ablation of the vascular supply, decreased osteoblast and increased osteoclast activity, replacement of biologically active red marrow with inactive yellow marrow, chondrocyte loss, 13 and direct destruction of collagen and inorganic matrix. 7 While the majority of radiation-associated osseous toxicity mechanisms result in delayed toxicity, acute toxicity due to direct injury to the bone matrix is possible.…”
Section: Discussionmentioning
confidence: 99%
“…14 Radiation has been shown to harm bone through numerous localized and systemic effects, often leading to ablation of the vascular supply, decreased osteoblast and increased osteoclast activity, replacement of biologically active red marrow with inactive yellow marrow, chondrocyte loss, 13 and direct destruction of collagen and inorganic matrix. 7 While the majority of radiation-associated osseous toxicity mechanisms result in delayed toxicity, acute toxicity due to direct injury to the bone matrix is possible.…”
Section: Discussionmentioning
confidence: 99%
“…Another key benefit of LDCT is the increased feasibility of radiological examinations in patients predisposed to other pathological skeletal conditions. It has been shown that patients undergoing cancer treatments, in the form of radiation therapy, experience insufficiency fractures43. As such, subjecting them to additional CT-based radiation for diagnostic evaluation of bone loss may not be practical, because of a probable risk of radiation-induced malignancy44 or fear of aggravated bone loss, leading to secondary bone fractures.…”
Section: Discussionmentioning
confidence: 99%
“…In bone tissue, ionizing radiation results in apoptosis of bone and endothelial cells, reduced metabolism, decreased vascularity and changes in remodeling (Pacheco and Stock, ). These changes result in modifications in the network of bone channels, reduction in bone matrix and amounts of calcium and phosphorus, and lead to biomechanical impairment and bone growth arrest (Rabelo et al, ).…”
Section: Introductionmentioning
confidence: 99%